A long term hydraulic stimulation study conducted at the Salak geothermal field. (November 2019) - Yoshioka, Keita; Pasikki, Riza; Stimac, Jim
Highlights: Comprehensive summary of the long term (>10 months) hydraulic stimulation study that took place at the Salak geothermal field, Indonesia. A series of pressure transient analyses show injectivity evolution. A thermo-hydro-mechanical model for injection response simulation and future performance forecast by the model. Abstract: Awi 18-1 is an injection well drilled in the Cianten Caldera, near the western margin of the Salak (Awibengkok) reservoir in west Java, Indonesia. As the initial well injectivity was low, a long-term hydraulic stimulation was conducted to improve the permeability and establish a better connection to existing natural fractures. A geologic model of the area was built by integration of surface mapping, log and core data, and well performance information. The well penetrated pre- and post-caldera volcanics, the caldera ring fault intrusion and contact metamorphic zone, and marine sedimentary rocks. Permeability was found primarily near the caldera margin in pre-caldera lavas and ring fault intrusion along steeply dipping N to NW and NE trending fractures that were partially sealed by mineral precipitation. A geomechanical simulation model was developed from the geologic model to understand the injectivity evolution mechanisms and behaviours under different injection conditions, and also predict long term future injectivity performance. The model domain contains the completed interval of a deviated injection well (Awi 18-1) and covers the majority of microseismic events observed during the course of the stimulation. It simulates injectivity evolution using fully coupled processes of heat and mass transfers in poro-elastic media. The model was history-matched against the injection data (i.e. pressure) by calibrating rock mechanical and fracture properties. A few what-if scenarios under different operation conditions were simulated to evaluate the effects of injection pressure and temperature on the injectivity. These what-if scenario simulations indicate that both colder injection temperature and higher wellhead pressure lead to better injection efficiency. Also, the higher pressure had prolonged impacts while the colder temperature impacts are limited at the early time.